Islam, Security and Television News - Flood, C. author. aut Link
X, 302 p.
Keywords: Focusing on British, French and Russian television news coverage of Islam as a security threat, this book provides the first comparative account of how television broadcasting in different geo- and socio-political environments integrates discourses on Islam into nationally oriented, representational systems.